Prevalence of microorganisms in cell phones and the behavioral pattern associated with the demographic of Dhaka City (South) - Reza, Mohammed Zawad (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.